Comparative Analysis of Risk Factors for Wasting among Under-Five Children in Urban and Rural Areas of East Nusa Tenggara - Loa, Welstin Wemi; Trisari Anggondowati; M Irzal, Mufti As Siddiq (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Introduction: Wasting, including wasted and severely wasted based on the weight-for-height index, remains a major public health concern in Indonesia. East Nusa Tenggara Province recorded the highest prevalence nationwide (15.9%) in 2024, highlighting persistent challenges in preventing child undernutrition. This study examined setting-specific factors associated with wasting among children aged 0–59 months in urban and rural areas of East Nusa Tenggara. Methods: A cross-sectional study was conducted using secondary data from the 2024 Indonesian Nutrition Status Survey (INSS), including 11,372 children aged 0–59 months. Wasting was defined as a Weight-for-Height z-score (WHZ) < −2 SD based on World Health Organization standards. Independent variables included child characteristics, infant and young child feeding practices, health status and healthcare access, parental characteristics, and household factors. Modified Poisson regression was used to estimate adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs). Results: Wasting prevalence was identical in urban and rural areas (15.5%). Low birth weight and short birth length were consistently associated with wasting in both settings. In urban areas, children aged 0–5 months had a lower prevalence of wasting (aPR= 0.43; 95% CI: 0.20–0.90), whereas low birth weight (aPR= 1.63; 95% CI: 1.15–2.30), short birth length (aPR= 1.35; 95% CI: 1.04–1.76), and low paternal education (aPR= 1.68; 95% CI: 1.20–2.35) increased the prevalence. In rural areas, wasting was associated with low birth weight (aPR= 1.64; 95% CI: 1.35–1.98), short birth length (aPR = 1.32; 95% CI: 1.11–1.57), male sex (aPR= 1.34; 95% CI: 1.18–1.53), and medium and low maternal education (aPR= 1.30 and 1.33, respectively). Conclusion: Although wasting prevalence was similar across settings, associated factors differed between urban and rural areas. Strengthening interventions to prevent adverse birth outcomes, while addressing setting-specific educational and socioeconomic determinants, may improve strategies to reduce wasting in East Nusa Tenggara.